Development of a fibre size-specific job-exposure matrix for airborne asbestos fibres. Issue 9 (5th November 2007) - Dement, J M; Kuempel, E D; Zumwalde, R D; Smith, R J; Stayner, L T; Loomis, D
Abstract : Objective: To develop a method for estimating fibre size-specific exposures to airborne asbestos dust for use in epidemiological investigations of exposure-response relations. Methods: Archived membrane filter samples collected at a Charleston, South Carolina asbestos textile plant during 1964–8 were analysed by transmission electron microscopy (TEM) to determine the bivariate diameter/length distribution of airborne fibres by plant operation. The protocol used for these analyses was based on the direct transfer method published by the International Standards Organization (ISO), modified to enhance fibre size determinations, especially for long fibres. Procedures to adjust standard phase contrast microscopy (PCM) fibre concentration measures using the TEM data in a job-exposure matrix (JEM) were developed in order to estimate fibre size-specific exposures. Results: A total of 84 airborne dust samples were used to measure diameter and length for over 18 000 fibres or fibre bundles. Consistent with previous studies, a small proportion of airborne fibres were longer than >5 μm in length, but the proportion varied considerably by plant operation (range 6.9% to 20.8%). The bivariate diameter/length distribution of airborne fibres was expressed as the proportion of fibres in 20 size-specific cells and this distribution demonstrated a relatively high degree of variability by plant operation. PCM adjustment factors also varied substantially across plant operations. Conclusions: These data provide new information concerning the airborne fibre characteristics for a previously studied textile facility. The TEM data demonstrate that the vast majority of airborne fibres inhaled by the workers were shorter than 5 μm in length, and thus not included in the PCM-based fibre counts. The TEM data were used to develop a new fibre size-specific JEM for use in an updated cohort mortality study to investigate the role of fibre dimension in the development of asbestos-related lung diseases.